Marie Curie, pioneer physicist - Greene, Carol (Chicago : Childrens Press, 1984)
A biography of the brilliant scientist whose work with radioactivity caused her death, but gave life to others.
Includes index.
Keywords: Curie, Marie, -- 1867-1934 -- Juvenile literature; Curie, Marie, -- 1867-1934.; Chemists -- Poland -- Biography -- Juvenile literature; Women chemists -- Poland -- Biography -- Juvenile literature; Chemists; Women -- Biography